Comparative assessment of Higherlife Foundation and Mavambo Trust’s contribution to the quality of education in Goromonzi district - Bere, Morris (Midlands State University, 2017)
This study is concerned with the role of NGOs in the provision of quality education in Zimbabwe. It specifically makes a comparative assessment of the contribution to quality education by Higherlife Foundation and Mavambo Trust, both local NGOs. The economic environment in Zimbabwe has impacted negatively on the quality of education that is offered by public or government schools, especially in rural areas. NGOs have come to the aid of the government in capacity building in the education sector. The involvement of NGOs in the education sector is hoped to contribute immensely to the quality of education. Most research work on the role of NGOs in the education sector has mostly covered work by international NGOs. There is little or no research that has looked at the contribution made by NGOs on the quality of education in Zimbabwe. Most research tend to look at the general role played by NGOs in the delivery of social services. In contrast to the above this research focuses on local NGOs. It specifically aims to establish the extent to which local NGOs have assisted the government in the effective provision of quality education.